A Dual-Chamber Leadless Pacemaker - Knops, Reinoud E; Reddy, Vivek Y; Ip, James E; Doshi, Rahul; Exner, Derek V; Defaye, Pascal; Canby, Robert; Bongiorni, Maria Grazia; Shoda, Morio; Hindricks, Gerhard; Neužil, Petr; Rashtian, Mayer; et al. (The New England journal of medicine, 2023)
BACKGROUND: Single-chamber ventricular leadless pacemakers do not support atrial pacing or consistent atrioventricular synchrony. A dual-chamber leadless pacemaker system consisting of two devices implanted percutaneously, one in the right atrium and one in the right ventricle, would make leadless pacemaker therapy a treatment option for a wider range of indications. METHODS: We conducted a prospective, multicenter, single-group study to evaluate the safety and performance of a dual-chamber leadless pacemaker system. Patients with a conventional indication for dual-chamber pacing were eligible for participation. The primary safety end point was freedom from complications (i.e., device- or procedure-related serious adverse events) at 90 days. The first primary performance end point was a combination of adequate atrial capture threshold and sensing amplitude at 3 months. The second primary performance end point was at least 70% atrioventricular synchrony at 3 months while the patient was sitting. RESULTS: Among the 300 patients enrolled, 190 (63.3%) had sinus-node dysfunction and 100 (33.3%) had atrioventricular block as the primary pacing indication. The implantation procedure was successful (i.e., two functioning leadless pacemakers were implanted and had established implant-to-implant communication) in 295 patients (98.3%). A total of 35 device- or procedure-related serious adverse events occurred in 29 patients. The primary safety end point was met in 271 patients (90.3%; 95% confidence interval [CI], 87.0 to 93.7), which exceeded the performance goal of 78% (P<0.001). The first primary performance end point was met in 90.2% of the patients (95% CI, 86.8 to 93.6), which exceeded the performance goal of 82.5% (P<0.001). The mean (±SD) atrial capture threshold was 0.82±0.70 V, and the mean P-wave amplitude was 3.58±1.88 mV. Of the 21 patients (7%) with a P-wave amplitude of less than 1.0 mV, none required device revision for inadequate sensing. At least 70% atrioventricular synchrony was achieved in 97.3% of the patients (95% CI, 95.4 to 99.3), which exceeded the performance goal of 83% (P<0.001). CONCLUSIONS: The dual-chamber leadless pacemaker system met the primary safety end point and provided atrial pacing and reliable atrioventricular synchrony for 3 months after implantation. (Funded by Abbott Medical; Aveir DR i2i ClinicalTrials.gov number, NCT05252702.).
Keywords: výsledek terapie; Pacemaker, Artificial; následné studie; Atrioventricular Block; Treatment Outcome; Humans; prospektivní studie; Prospective Studies; kardiostimulátor; srdeční arytmie; kardiostimulace umělá; atrioventrikulární blokáda; Atrial Fibrillation; fibrilace síní; Arrhythmias, Cardiac; Follow-Up Studies; lidé; Cardiac Pacing, Artificial